(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Food waste is a big issue which needs to be tackled by the hospitality industry. The impact of food waste is not just financial. It has an enormous impact on the environment; it affects the overall atmosphere of the world. The study details out the various measures taken by the Institute of Hotel Management, Pusa, New Delhi in reducing food waste at various levels of food preparation. Objective: The objective was to reduce production and plate waste. Methods:Various methods such as sensitizing students, involving human resource, portion control measures, introduction of Root to Stem concept, combo meals, vegetarian cooking and inventory management were implemented to control food wastage. Results: With introduction of Root to Stem concept, 33% of vegetable and fruit cost was reduced in the month of March 2016. The average plate waste for 550 students was just 141 gm. Conclusion: The industry can also look into the idea of redesigning its menu and also innovative concepts such as “Root to Stem” cooking to cut down on the amount of food being thrown down the drain.